Evaluation of carbonated product from mineral carbonation of mining waste for carbon sequestration - Abdullah, Umi Rukiah; Kusin, Faradiella Mohd; Wan Ab Karim Ghani, Wan Azlina (Malaysian Institute of Planners, 2024)
Mining operations generate significant quantities of waste containing alkaline earth silicates, which are valuable for carbon sequestration. Hence, the goal of this study is to assess the possibility of using mining waste to store carbon through a process of mineral carbonation. The study tested mineral carbonation under low reactivity conditions, including ambient pressure and low temperature, to evaluate the effect of pH levels on process efficiency. The samples were discovered to have an alkaline pH, suggesting that they were suitable for mineral carbonation reactions from the beginning. The carbonation process of the mineral was conducted at different pH levels of 8, 10, and 12. The findings showed that the carbonation efficiency was approximately 3%, with the highest level observed at pH 12. Through thermogravimetric analysis, it was observed that there was a multi stage transformation of minerals, which indicated the formation of carbonates containing iron and magnesium. The process captured approximately 33 and 39 g of CO2/kg. The process indicates that mine waste can be used as a source material for mineral carbonation, as demonstrated by the formation of iron and calcium carbonate products. This research demonstrates that mine waste has the potential for long-term carbon storage, offering a beneficial method for waste management and carbon capture strategies.